Optimal Reconfiguration of Network with Variant Transmission Times on Arcs - Gupta, Shiva P.; Pyakurel, Urmila; Dhamala, Tanka Nath (The Nepali Mathematical Sciences Report, 2023)
Contraflow means lane reversals on networks. In lane reversal reconfiguration, the capacity of the arc increases by reorienting arcs towards demand nodes, which maximizes the flow value and reduces the travel time. In this work, we survey the existing pieces of literature on single and multi-commodity contraflow problems with symmetric and asymmetric travel times on parallel but oppositely oriented edges. Many illustrations are included to support the main results.